Vitaliy Sushchansky (11.11.1946 – 29.10.2016) (Algebra and Discrete Mathematics, 2017)
Vitaliy Ivanovych Sushchansky was born on November 11, 1946 in Khodorkiv in Zhytomyr region west of Kyiv. He died half a month before his seventieth birthday on October 29, 2016 in Gliwice, Poland. He was an outstanding mathematician and teacher, one of the most prominent researchers in group theory in Ukraine and Poland